COLIBACTIN-PRODUCING E. COLI AND ITS CORRELATION WITH COLORECTAL CANCER IN KAZAKHSTANI PATIENTS - Surdeanu , A.K.; Kurentay , B.A.; Gusmaulemova , A.D.; Bayanbek , D.S.; Kulmambetova , G.N. (Eurasian Journal of Applied Biotechnology, 2025)
In recent years, increasing evidence has confirmed the importance of intestinal dysbiosis in the development and progression of colorectal cancer (CRC). Particular attention is paid to colibactin-producing Escherichia coli, which is considered one of the key microbial factors in carcinogenesis. Colibactin-producing Escherichia coli carries the pks pathogenicity island encoding the low-molecular genotoxin colibactin. This toxin has a pronounced cytotoxic effect on intestinal epithelial cells, causing double-strand DNA breaks and cell cycle arrest. Such damage contributes to the development of genomic instability, which ultimately increases the risk of colorectal cancer. The aim of our study was to determine the clinical role of pks+ E. coli in the development and progression of CRC in Kazakhstani patients. Biopsies of the intestinal mucosa were obtained from 113 patients of the National Scientific Oncology Center with a confirmed diagnosis of colorectal adenocarcinoma from three sites (tumor, adjacent tumor-unaltered area, and distally located healthy area). To detect marker genes of colibactin (clbA, clbB, clbQ) in the selected biomaterial, quantitative PCR and routine PCR methods were used. A comprehensive assessment of the relationship between the carriage of pks+ Escherichia coli and such factors as tumor size and location, consumption of red and processed meat, the presence of bad habits, as well as metabolic and somatic diseases in patients was carried out. Our results demonstrated that colibactin-producing E. coli was detected in 60% of tumor tissue biopsies, 53% of tumor-adjacent samples, and 54% of distal intestinal mucosa biopsies in cancer patients (P> 0.05). A statistically significant relationship was found between pks+ Escherichia coli carriage and tumor size in patients with CRC (P=0.009). This may indicate that pathogenic E. coli strains act not only as driver microorganisms initiating colon carcinogenesis, but also as potential long-term colonizers of tumor tissue involved in the pathogenesis and progression of the disease at later stages.